1996
DOI: 10.2527/1996.74102310x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dietary forage level and forage coarseness of grind on growth performance and digestive function in feedlot steers.

Abstract: We conducted two trials to examine the influence of dietary forage level (FL; 16 and 8% sudangrass hay) and forage coarseness of grind (COG; ground to pass through a 2.5- vs 7.6-cm diameter screen) on growth performance and digestive function in feedlot steers fed a steam-flaked corn-based finishing diet. Thirty-two Mexican crossbred steers (297 kg) were used to determine treatment effects on growth performance during an 80-d finishing period. There were no treatment interactions (P > .10). Reducing FL increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
16
2
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 17 publications
6
16
2
2
Order By: Relevance
“…Therefore, the animals were not weighed in a manner that would provide data to evaluate protein weight gain based on N retention. The significant improvement of N retention and digestibility was consistent with other previous trials (Calderon-Cortes and Zinn, 1996;Fimbres et al, 2002b). Fimbres et al (2002b) reported that N retained was positively related to dietary energy density and inversely related to dietary hay level.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Therefore, the animals were not weighed in a manner that would provide data to evaluate protein weight gain based on N retention. The significant improvement of N retention and digestibility was consistent with other previous trials (Calderon-Cortes and Zinn, 1996;Fimbres et al, 2002b). Fimbres et al (2002b) reported that N retained was positively related to dietary energy density and inversely related to dietary hay level.…”
Section: Discussionsupporting
confidence: 90%
“…However, Gorocica-Buenfil and Loerch (2005), reported that dietary rice straw did not influence apparent total-tract OM and NDF digestibility in steers when 13% maize silage was replaced by maize. Similarly, other previous studies (Zinn et al, 1994;Calderon-Cortes and Zinn, 1996) have demonstrated that replacing 8% Sudan grass with maize did not affect the ruminal disappearance of OM and NDF in steers. These results indicate that the effect of dietary rice straw on OM and NDF digestion in forestomach and post-digestive tract probably depends upon animal species.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Similar responses in DMI between diets containing different levels of forage have been observed previously in trials involving steam-flaked corn-based diets (Zinn et al 1994;Calderon-Cortes and Zinn 1996). As the S:ADF ratio increased, the DMI, ADG, G:F and NE of diet increased (P ≤ 0.03) linearly.…”
Section: U and S:adf Ratio Effects On Growth Performance And Dietary supporting
confidence: 80%